Barriers for the use of outdoor gyms in adults and elderly from a southern city of Brazil - Bergmann, Gabriel Gustavo (2020)
The aim of this study was to identify barriers to use Outdoor Gyms (OGs) for physical activity (PA) practice and to examine their association with leisure-time PA, demographic and socioeconomic variables in adults and elderly. This cross-sectional population-based study enrolled 431 adults and elderly (66.8% women) aged 18 to 87 years living in the surroundings (up to 500 meters) of four OGs. Information about using OGs for PA practice, barriers to use OGs, leisure-time PA, demographic and socioeconomic variables were collected by domiciliary interview. Associations between barriers to use OGs with other included variables were analyzed using Chi-Square test. None barriers was reported for 29.2% (95%CI: 24.9-33.5) of the participants, being almost of then OGs’ users. The most reported barriers to use OGs were lack of time (21.6%; 95%CI: 17.7-25.5), lack of interest (16.5%; 95%CI: 13.0-20.0) and laziness (10.7%; 95%CI: 7.8-13.6). Intrapersonal barriers were more often among men, interpersonal among women and environmental among those with less educational level (p < 0.05). In conclusion, OGs’ users perceived fewer barriers than non-users, and most barriers to the use of OGs were intrapersonal with lack of time being the most prevalent.